Coordinating negotiations in data-intensive collaborative working environments using an agent-based model-driven platform - Jardim-Gonçalves, R.; Cretan, A.; Coutinho, C.; Agostinho, C.; Bratu, B. (Enterprise Information Systems, 2018)
This paper tackles the interoperability problems of enterprise information systems by presenting a distributive model-driven platform for parallel coordination of multiple negotiations in data-intensive collaborative working environments. The proposed model was validated and verified by an industrial application scenario within the European research project H2020 C2NET (Cloud Collaborative Manufacturing Networks). This real scenario developed data-intensive collaborative and cloud-enabled tools that allow the optimisation of the supply network of manufacturing SMEs, proposing a negotiation solution based on a model-driven interoperable decentralised architecture.